Case report: B7-H3 CAR-T therapy partially controls tumor growth in a basal cell carcinoma patient - Hu, Gang; Li, Guangchao; Wen, Wei; Ding, Wen; Zhou, Zhao; Zheng, Yongwei; Huang, Taoyuan; Ren, Junnan; Chen, Rongyi; Zhu, Dingheng; He, Renliang; Liang, Yunsheng; et al. (Frontiers in Oncology, 2022)
B7-H3 is over-expressed in multiple types of solid tumors, making it an ideal target for chimeric antigen receptor (CAR)-T therapy. Here we first report a case of multiple basal cell carcinoma (BCC) patient treated with humanized monoclonal anti-B7-H3 CAR-T cells through direct intra-tumor injection. After three dose-escalated injections, the lesion in the abdomen decreased by 40% in volume, shrank from bulging to flat, but was not eradicated completely. The large lesion in the forehead became dry from original ulcer and bleeding. The adverse events observed were itching, myalgia and redness. Immunohistochemistry analysis demonstrated that B7-H3 positive tumor cells and B7-H3 expression intensity were reduced after injections of CAR-T cells. The number of infiltrating CD3 T cells increased significantly but mainly located outside the tumor region. Subsequently, high levels of TGF-β in the tumor area were observed, suggesting that solid tumor microenvironment may hinder the infiltration and effect of CAR-T cells. In summary, in this particular case report, intra-tumor injection of B7-H3 CAR-T cells partially controls tumor growth in BCC patient with minor adverse events. The efficacy and safety of B7-H3 CAR-T therapy need to be further investigated with a larger cohort of patients. Although only one clinical case is reported here, the anti-B7-H3 CAR-T cell therapy should be considered as a treatment option for solid tumors in the future.